Comparative Plasma and Interstitial Fluid Pharmacokinetics of Meloxicam, Flunixin, and Ketoprofen in Neonatal Piglets - Nixon, Emma; Almond, Glen W.; Baynes, Ronald E.; Messenger, Kristen M. (Frontiers in Veterinary Science, 2020)
Piglet castration and tail-docking are routinely performed in the United States without analgesia. Pain medications, predominately nonsteroidal anti-inflammatory drugs, are used in the EU/Canada to decrease pain associated with processing and improve piglet welfare, however, past studies have shown the efficacy and required dose remain controversial, particularly for meloxicam. This study assessed the pharmacokinetics of three NSAIDs (meloxicam, flunixin and ketoprofen) in piglets prior to undergoing routine castration and tail-docking. Five-day-old male piglets (8/group) received one of 3 randomized treatments; meloxicam (0.4 mg/kg), flunixin (2.2 mg/kg), ketoprofen (3.0 mg/kg). Two hours post-dose, piglets underwent processing. Drug concentrations were quantified in plasma and interstitial fluid (ISF) and pharmacokinetic parameters were generated by noncompartmental analysis. Time to peak concentration (Tmax) of meloxicam, flunixin and S(-)-ketoprofen in plasma were 1.21, 0.85 and 0.59h, compared to 2.81h, 3.64h and 2.98h in the ISF, respectively. The apparent terminal half-life of meloxicam, flunixin and S(-)-ketoprofen were 4.39, 7.69 and 3.50h, compared to 11.26h, 16.34h and 5.54h, respectively in the ISF. If drug concentrations in the ISF are more closely related to efficacy than the plasma, then the delay between the Tmax in plasma and ISF may be relevant to the timing of castration in order to provide the greatest analgesic effect.